Fetal Outcome of Term Pregnancy with Non-Reactive Non-Stress Test at Birat Medical College Teaching Hospital - Deo, Amit; Mahato, Raj Deb; Subedi, Ram Bhakta; Pradhan, Tarun (Birat Journal of Health Sciences, 2021)
Introduction: Non-stress test (NST) in pregnancy helps to detect fetuses which are at risk of developing hypoxia. In general, reassuring NST indicates good fetal outcome while non-reassuring NST may result in abnormal perinatal outcome.Objectives: The objective of this study is to detect the fetal outcome among term uncomplicated pregnancies with Non-reactive NST in Birat Medical College Teaching Hospital.Methodology: A cross-sectional study conducted for 6 months in the department of Obstetrics and Gynaecology at Birat Medical College Teaching Hospital. Singleton pregnancies with longitudinal lie and cephalic presentation between 37 to 42 weeks Period of gestation were included in the study. All participants were advised for a NST as an institutional protocol for 20 minutes at the time of admission. Participants with Non-reactive NST were counselled and planned for emergency LSCS as per hospital protocol. Participants were followed up for intraoperative findings such as colour of liquor and umbilical cord abnormality and outcome of fetus were assessed for APGAR score and need for NICU. The collected data was entered in Microsoft Excel and analyzed by using SPSS version 22.Results: Out of 115 pregnant women, the mean age and standard deviation of 24.93±4.68 years. Decelerations was found in 35(30.4%), Decreased baseline variability was found in 33(28.7%), Persistent fetal tachycardia was found in 23(20%) and Decreased baseline fetal heart was found in 24(20.9%). Intraoperative meconium-stained liquor was found in 39(33.9%) of patients. All babies born were shown APGAR score > 7 at 5 minutes. 14(12.2%) babies were admitted to the Neonatal intensive care unit (NICU). Correlation of admission NST was not found statistically significant with fetal outcome.Conclusion: LSCS for abnormal NST does not show adverse fetal outcome.